2016
DOI: 10.1016/j.bmcl.2016.09.028
|View full text |Cite
|
Sign up to set email alerts
|

A new selective fluorescent probe based on tamoxifen

Abstract: Developing targeted validation probes that can interrogate biology is of interest for both chemists and biologists. The synthesis of suitable compounds provides a means for avoiding the costly labeling of cells with specific antibodies and the bias associated with the interpretation of biological validation experiments. The chemotherapeutic agent, tamoxifen has been routinely used in the treatment of breast cancer for decades. Once metabolized, the active form of tamoxifen (4-hydroxytamoxifen) competes with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Furthermore, unlike EG and DEG, the effects of TEG on the renal system are transient and minor [46]. To label NDMT with the linker TEG, the free amine of NDMT 1 was reacted with TEG-OTs 2, which was prepared in-house following previously reported procedures [47,48], using basic conditions in CH 3 CN at reflux to give TAM-TEG conjugation 3. Finally, mesylation of the terminal alcohol group was achieved using methanesulfonyl chloride (MsCl) to give the requisite TAM-TEG-OMs 4 building block for attachment to the MSN material (see Materials and Method for full reaction conditions).…”
Section: Synthesis Of Tam-teg-omsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unlike EG and DEG, the effects of TEG on the renal system are transient and minor [46]. To label NDMT with the linker TEG, the free amine of NDMT 1 was reacted with TEG-OTs 2, which was prepared in-house following previously reported procedures [47,48], using basic conditions in CH 3 CN at reflux to give TAM-TEG conjugation 3. Finally, mesylation of the terminal alcohol group was achieved using methanesulfonyl chloride (MsCl) to give the requisite TAM-TEG-OMs 4 building block for attachment to the MSN material (see Materials and Method for full reaction conditions).…”
Section: Synthesis Of Tam-teg-omsmentioning
confidence: 99%
“…The procedure was adapted and modified from two previously published methods [47,48]. A mixture of 1 (113.…”
Section: Synthesis Of (mentioning
confidence: 99%
“…The ability of TAM to be a targeting agent was first proven by its ability to deliver fluorescent dyes into tumours, through the conjugation of TAM with various fluorophores, as seen in Figure 8. In a study conducted by Ho et al [135], a novel ER+ targeted fluorescent probe was prepared which obviated the need for costly labelling of cells with specific antibodies. The TAM-BODIPY ® FL probe employs a tetraethylene glycol (TEG) unit as the linker between targeting vector (TAM) and fluorophore, as demonstrated in Figure 8, and exhibited selective binding to ER+ and ER-cell lines [135].…”
Section: Tam As a Targeting Vectormentioning
confidence: 99%
“…In a study conducted by Ho et al [135], a novel ER+ targeted fluorescent probe was prepared which obviated the need for costly labelling of cells with specific antibodies. The TAM-BODIPY ® FL probe employs a tetraethylene glycol (TEG) unit as the linker between targeting vector (TAM) and fluorophore, as demonstrated in Figure 8, and exhibited selective binding to ER+ and ER-cell lines [135]. Even though this probe showed no affinity for TAM resistant BC cell lines, it still offered a useful insight into the biology of cancer cells.…”
Section: Tam As a Targeting Vectormentioning
confidence: 99%
“…Ho et al reported the synthesis of fluorescent conjugate BODIPY®FL of tamoxifen linked through an ethylene glycol moiety (Scheme 96). [99] The tertiary amine group of tamoxifen (489) was demethylated using α-chloroethyl chloroformate afforded compound 490 as quaternary ammonium salt in 91% yield which on further reaction with monotosylated polyethylene glycol 491 gave tertiary amine E-492 in less yield (55%). The terminal hydroxyl group of E-492 was further tosylated to give compound E-493 in 75% yield which on substitution with thioacetate offered E-494 in the yield of 46%.…”
Section: Nucleophilic Substitution Reactionmentioning
confidence: 99%